APPLICATION OF PROFILE MATCHING METHOD AS THE ELECTION OF PRIVATE UNIVERSITIES IN MEDAN FOR SMK STUDENTS - Lavenia Ulandari; Purwa Hasan Putra (Jurnal Ipteks Terapan, 2020)
Profile Matching Method outline is the process of comparing individual competencies into system competency standards so that the results of competency comparison can be known. Decision Support System or Decision Support System which we then briefly in this thesis becomes SPK, is generally defined as a system that is able to provide good capabilities, problem-solving abilities, and communication skills for semi-structured problems. Specifically, the DSS is defined as a system that supports the work of a manager in solving semi-structured problems by providing information or proposals leading to certain decisions. From this description the authors designed a decision support system to help vocational students in the selection of private universities in Medan